MOTIVASI BELAJAR ANAK TUNARUNGU DI SEKOLAH INKLUSIF: KAJIAN STUDI LITERATUR - -, Friska Y. N. Hutasohit; Adinda Nabila; Chairani Dwi Putri; Nazma Aliyah; Vika Maria Sagala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine in depth the learning motivation of deaf children in the context of inclusive schools through a literature study approach. Deaf children have special characteristics that affect the way they receive and process information, so they need adaptive learning strategies to increase their learning motivation. Learning motivation is one of the key factors that affect student engagement, achievement and social-emotional development. This study provides important implications for educators and policy makers in developing more inclusive and responsive learning practices.